PENERAPAN TERAPI KOMPRES DINGIN PADA PASIEN POST ORIF DENGAN MASALAH KEPERAWATAN NYERI AKUT - Novita, Yoli; Kharisna, Dendy; Wardah, Wardah; Dewi, Sarina (Yayasan Healing and Healthcare Education, 2024)
One of the treatments used to treat fractures is surgery or surgery. The effects of this surgery can cause pain to the patient. Therefore, it is necessary to carry out proper management so that patients are able to control the pain they feel. Pain control measures can be carried out in non-pharmacological ways such as cold compress therapy. Cold compresses help in compressing and slowing down the transmission of pain nerves. The purpose of implementing this case study is to apply cold compress therapy to post-ORIF patients in the Edelweis room of Arifin Achmad Hospital, Riau Province. The procedure is performed on one patient for 10 minutes once a day for 3 days. Before and after the procedure, we measure the patient's pain scale using the Numeric Rating Scale (NRS). The indicators assessed include complaints of pain, grimacing, alertness, restlessness, sleep disturbances, and pulse. From this application, an average reduction in the patient's pain scale was obtained by 4. The results of applying cold compresses can help to reduce pain in post-ORIF patients. Thus, nurses can make cold compress therapy a form of nursing action in the nursing care of post-ORIF patients.